Scritture femminili e Storia Female Writings and History - Laura Guidi (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2004)
This book gathers together the papers presented at the conference "Female Writings and History (18th-19th cent.)". The conference was organized in May 2003 at the Department of History, in cooperation with the Ph.D. Program in Gender Studies, the Pole of Humanities and Social Sciences of Federico II University, and the Neapolitan Society of National History.